G259 Delivering nurse-led emergency paediatric care in sierra leonean hospitals: the effect on quality of care and mortality. (12th March 2018) - Hands, C; Dankwa, S; Murray, M; Kenyon, P; Doherty, S; Goldberg, K; Bailey, E; Taylor, S
Abstract : Aims: To assess the impact of a national programme in paediatric secondary care, to introduce ETAT protocols and train nursing staff to lead emergency management. Methods: Within a wider strategy to reduce child mortality, the Sierra Leone Ministry of Health and Sanitation engaged WHO and RCPCH to introduce WHO Emergency Triage Assessment and Treatment (ETAT) protocols to all district hospitals. Two clinical mentors (one Sierra Leonean, one UK/international) were placed at each hospital for six months, and delivered a three-month teaching programme with a written and practical examination, as well as hands-on clinical mentorship. Upon passing the examination, nurses were awarded the right to assess, prescribe for, and treat emergency paediatric cases. The mentors collected treatment data each day on children admitted the previous day, and followed each child to record their discharge outcome. This programme monitoring data was analysed to identify compliance with clinical protocols, and to calculate mortality rates. The programme delivery period was split into seven four-week blocks, and compliance rates and mortality rates were calculated for each four-week period. Results: We analysed monitoring data from three regional hospitals in the first phase of roll-out (table 1). The combined mortality rate across the three hospitals fell from 15% in the first four-week period, to 4% in the final period. This fall was accompanied by improvements in key areas of compliance with WHO ETAT standards. Conclusion: This study suggests that implementation of ETAT protocols and delivery of improved quality of care and decreased mortality may be achievable with an effective and cost-efficient nurse-led model for emergency paediatric care in low-resource settings.